Identification of Elemental Composition and Heavy Metal Content in Maninjau Lake Sediment Using X-Ray Fluorescence (MNJ 18-41B) - Fajar Akmal; Hamdi Rifai; Syafriani Syafriani; Caroline Bouvet De La Maisonneuve; Jeffrey Anthony G. Oalmann; Francesca Forni; Steffen Eisele; Marcus Phua; Rizaldi Putra (Universitas Negeri Malang, 2021)
Maninjau Lake is a caldera lake located in Agam, West Sumatra. This lake was formed from the volcanic activity of Mount Maninjau Purba about 60,000 years ago. The volcanic material resulting from the eruption is scattered and deposited in various places, one of which is in lake sediments. Volcanic ash contains various types of elements, including heavy metal elements. This study aims to determine the composition and content of heavy metal in the sediments of Maninjau Lake. The sample analyzed was MNJ 18-41B with a core length of 440 mm, focusing on specimens 148 mm and 376 mm. The selection is a specimen based on the magnetic susceptibility value obtained from the measurement meter susceptibility of the MS2E. Specimen 148 has a value susceptibility low of 2.1 × 10-8 m3/kg, while the 376 specimens have the highest value of susceptibility, the highest 141 × 10-8 m3/kg. The content of sediment elements was determined using the results of X-Ray Fluorescence (XRF) measurements. The measurement results showed that the mineral-forming elements in the sediments of Lake Maninjau were dominated by Si, Fe, Rh, and Zr. In contrast, the highest heavy metal elements are Mn, Fe, Sr, and Rh. Based on the elemental composition and mineral oxide compounds in the sediments of Lake Maninjau derived from volcanic ash.DOI: 10.17977/um024v6i22021p068